'Cantik' as architecture stage in Islamic contemporary / Yuke Ardhiati - Ardhiati, Yuke (2012)
'CANTIK' in Nusantara term has a depth of meaning as non-material thing as a soul in beauty called "Cantik luar-dalam'. Based on Phenomenology in Grounded Theory found a shift paradigm of 'CANTIK' as part of "Architecture's Stage" or "Arsitektur Panggung" as something metaphysical found as Islamic contemporary icons in Architecture, Art, and Culture, by built monumentally and spectacular as Zaha Hadid and Norman Foster in Mecca. In other side, Ridwan Kamil in Bumi Parahyangan created the new architecture design of mosque without a "crown‟ to express modernity of Moslem within sustainable in nature.